RATU BALQIS DALAM NARASI SEMIOTIKA AL QUR’AN - Fathurrosyid, Fathurrosyid (UIN Sunan Kudus, 2013)
Penelitian ini membahas perspektif wacana dan hubungan gender dalam Al-Qur’an, terutama di wilayah publik politikdengan menggunakan kisah objek formal, Ratu Balqis di Kerajaan Saba’ di Qs. al-Naml (27): 29-44.Menerapkan semiotika yang memberi arti dan maknayang mampu merekonstruksi pemahaman yang telah terkesan kaku dan eksklusif pada kisah Ratu Balqis.Melalui pemahaman semiotik, hubungan antara pria dan wanita mengacu pada simbol kesetaraan gender di antara mereka. Dalam konteks ayat-ayat ini Ratu Balqis ternyata menjadi simbol feminis sejati dengan menjelaskanketaatan dan penyerahan dirinya hanya untuk Allah swt,bukan untuk Nabi Sulaiman. Karena keduanya adalah hamba Allah swt yang tidak boleh mengklaim dirinya superior, sementara yang lain ditekan sebagai inferior.Keterlibatan Nabi Sulaiman dalam pengakuan Balqi sadalah hanya sebagai aktor dan mediator yang membuat mereka mengadopsi teologi monotheisme.kata kunci: Semiotika, Al-Qur’an, Ratu Balqis, Gender. This study tried to dismantle the discourse and genderrelations perspective of the Qur’an, especially in thepublic-political region by using formal object tale, of Queen Balqis in the Kingdom of Saba’ on Qs. al-Naml(27):29 - 44. Applying semiotics that signed meaning andsignificance was able to reconstruct the understanding which has been impressed rigid, exclusive and misogynicon the story of Queen Balqis. Through a semiotic understanding, relationships between men and women refer to the gender equality symbols between them. Inthe context of these verses, Queen Balqis turned outto be a true feminist symbol through clarifying herobedience and submission only to Allah swt, not toProphet Solomon. Because both are the servants of Allahswt that should not be claiming to be the superior, whileothers are suppressed as the inferior. The involvement of Prophet Solomon in Balqis’ confession was merely as theactor and mediator that made them adopting a theology of monotheism.Keywords: Semiotics, Al-Qu’an, Queen Balqis, Gender